Towards a black poetics: alternative modes of visibility in representations of post-apartheid black trauma - Hendricks, Sabeela (Department of English Language and Literature, 2025)
Over the years, literary scholarship has revealed writers' creative attempts to represent the experiences of marginalised groupsthat have been disregarded by legacies of colonial violence. Conscious of the genealogy of Black women poets who have contributed to South Africa's literary landscape, I make a case for poetry's restorative function with the aim of offering an intervention in the fields of post-colonial criticism and trauma studies. I critically explore how specific poetic techniques employed in the collections of Koleka Putuma (2021), Gabeba Baderoon (2018), and Maneo Mohale (2019) allow for the historical trauma of Black women to be attended to in the contemporary moment. These collections provide a basis from which to examine how a poetic reimagining prevents the textual revival of colonial violence, whilst simultaneously resisting historical erasure by bringing the voices of Black women to the forefront. Through close analysis of the aforementioned works, I draw attention to various modes of visibility as a way to illuminate how all three poets under review make use of certain strategies and creative interventions in order to craft new parameters for calling Black experience into sight. I suggest that the artistic commitment of reaffirming Black experiences can be productively understood through particular engagement with Black poetics. Drawing from scholars like Makhosazana Xaba, Barbara Boswell, Pumla Gqola, Saidiya Hartman, and Audre Lorde, I identify the poems' modes of visibility according to three main tropes: the physical body, domestic spaces, and South Africa's botanical landscape. These representational forms radically depart from conventional traditions of knowledge-making and instead, facilitate an active shift in readers' attention by emphasising the capacity of poetic language to make visible the localised histories of marginalised communities in ways that are ethical. Bearing these poetic strategies in mind, I have focused on recentring the representational medium of poetry as a valuable and generative literary form through which the historical trauma of colonialism and apartheid can be articulated, and have consequently sought to emphasise the need to recognise creative sites asspaces where theoretical frameworks are produced, and not merely applied.